Teaching Foreign Trade in English Through the Modalities Based on Competences and Using Moodle - Ana María Correa Díaz (Profile Issues in Teachers' Professional Development, 2012)
With the new approach to guide the learning process of students with a model based on the development of competences, and in comparison with the traditional lecture-based learning, it is necessary to start working with the teaching modalities that help to achieve this objective. With that in mind, the aim of the study reported in this article was to show that through the use of active teaching methods focusing on the development of competences we can improve the writing, speaking and research competences in English of the students who nowadays take university subjects in a foreign language in Colombia. The results showed that the support provided by the platform promotes student motivation in carrying out their self-learning, which contributes to the development of the mentioned competences.